THE ROLE OF INFLAMMATORY MARKERS IN THE EARLY DIAGNOSIS OF SEPSIS (International journal of artificial intelligence, 2026)
Sepsis is a life-threatening condition resulting from the body's extreme response to infection. Early diagnosis is crucial to reduce morbidity and mortality. Inflammatory markers, such as C-reactive protein (CRP), procalcitonin (PCT), and interleukins, play a vital role in the early identification and management of sepsis. This study investigates the diagnostic value of these biomarkers in patients with suspected sepsis in intensive care units (ICUs).